Single Molecule Magnets of Co2 and Co2La MOFs Synthesized by New Schiff Base Ligand N,N′-bis(o-Vanillinidene) Ethylenediamine (o-VEDH2) - Ghosh, Mithun Kumar; Jana, Barun; Ghorai, Tanmay Kumar (Frontiers in Chemistry, 2020)
Schiff base ligand N,N′-bis(o-vanillinidene) ethylenediamine (o-VEDH2) has been employed to synthesize new [CoIICoIV(o-VED)(OAc)2(μ2-OAc)(OMe)]•MeOH (1) and [Co2IV(o-VED)2(en)2(NCCH3)(OCH3)][La(NO3)6](NO3−)•2MeOH•MeCN•H2O (2) metal–organic frameworks (MOFs) that have interesting single molecule magnets (SMMs) property. The synthesized complexes are characterized by single crystal X-ray diffraction, fourier transform infrared spectroscopy (FTIR), UV-visible spectroscopy, and squid magnetic measurement. Single crystal X-ray data show that both complexes crystallize in the monoclinic crystal system with P21/c(14) and P21/n(14) space groups and generate unique MOF-like structures. Overall, both the metal centers of 1 form octahedral geometry with a butterfly core structure. Variable temperature (T) and field (H) solid-state direct-current (dc) and alternative current (ac) magnetic susceptibility measurements were performed on both the complexes over 1.8 to 300 K, which exhibited a ground state spins (S) of 4 and 5 of complexes 1 and 2, respectively. The AC out-phase and in-phase properties of complexes show SMMs. Other properties such as optical, sensing, and DNA-binding interactions were also investigated by the complexes. Complexes 1 and 2 have energy band gaps of 3.7 and 3.03 eV indicating semiconductor properties. Simultaneously, complex 1 was found to sense H2O2 with a rate constant (k) = 1.59 × 10−4 s−1, whereas complex 2 was found to bind with calf-thymus–DNA by intercalation mode with binding constant (Kb) of 1.22 × 105 M−1.